Quelques enseignements récents de la réforme du système monétaire international - Decaluwé, Bernard (L'Actualité économique, 1979)
It is now recognized that a viable international monetary system must rest on a combination of only two of the following three principles: (1) respect of the national economic policies, (2) free convertibility of currencies, (3) fixed parities with gold and the dollar. The author emphasizes some arguments against flexible exchange rates. He concludes that the present international monetary system has resolved the fundamental ambiguity of the Bretton Woods system by permitting flexibility of exchange rates.